The Release of Substance P From Cultured Dorsal Root Ganglion Neurons Requires the Non-neuronal Cells Around These Neurons - He-Bin Tang; Yu-Sang Li; Yoshihiro Nakata (Journal of Pharmacological Sciences, 2007)
Substance P is known to be released from dorsal root ganglion (DRG) neurons, but the possible involvement of non-neuronal cells in the process of substance P release is not known. During the culture period, the number of surviving DRG neurons, the total substance P content from the culture medium and DRG cells, and the total protein of DRG cells were monitored. Both the number of surviving neurons and the total substance P content decreased in a time-dependent manner, whereas the total protein synthesis was increased. The localization of substance P in small-to-medium–sized neurons was further confirmed by immunocytochemistry. Finally, the substance P release levels from the neuronal and non-neuronal enrichments were investigated by radioimmunoassay. Both partially purified DRG neurons and non-neuronal cells exhibited a weaker substance P release response to capsaicin or KCl, relative to unpurified DRG cells. The total substance P content from the partially purified DRG neurons was almost the same as that from the unpurified DRG cells, but much more than that from the partially purified DRG non-neuronal cells. These findings suggest that substance P is released from DRG neurons, and this process should require the coexistence of neurons and non-neuronal cells. Keywords:: capsaicin, dorsal root ganglion (DRG) neuron, non-neuronal cell, substance P content, substance P release